2016
DOI: 10.3390/molecules21020227
|View full text |Cite
|
Sign up to set email alerts
|

Screening and Analysis of the Potential Bioactive Components of Poria cocos (Schw.) Wolf by HPLC and HPLC-MSn with the Aid of Chemometrics

Abstract: Abstract:The aim of the present study was to establish a new method based on Similarity Analysis (SA), Cluster Analysis (CA) and Principal Component Analysis (PCA) to determine the quality of different samples of Poria cocos (Schw.) Wolf obtained from Yunnan, Hubei, Guizhou, Fujian, Henan, Guangxi, Anhui and Sichuan in China. For this purpose 15 samples from the different habitats were analyzed by HPLC-PAD and HPLC-MS n . Twenty-three compounds were detected by HPLC-MS n , of which twenty compounds were tentat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(51 citation statements)
references
References 30 publications
3
36
0
Order By: Relevance
“…Accumulating studies have demonstrated that place of origin could significantly affect quality of the materials since climate and environment influence biosynthesis and accumulation of secondary metabolites in organism [ 18 ]. The origin places of PC are also multiple; in China, PC mainly grows in Yunnan, Hubei, Anhui, Henan and Hunan Provinces [ 19 , 20 , 21 ]. However, whether and how the quality of PCS differs according to collection location have largely not been determined.…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating studies have demonstrated that place of origin could significantly affect quality of the materials since climate and environment influence biosynthesis and accumulation of secondary metabolites in organism [ 18 ]. The origin places of PC are also multiple; in China, PC mainly grows in Yunnan, Hubei, Anhui, Henan and Hunan Provinces [ 19 , 20 , 21 ]. However, whether and how the quality of PCS differs according to collection location have largely not been determined.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, chemometrics have attracted increasing attention with the development of data mining methodologies, which could simplify complex data and find hidden information. Hierarchical cluster analysis (HCA), principal component analysis (PCA), and partial least squares discriminant analysis (PLS-DA) have been applied to discriminate the class and evaluate the quality of traditional Chinese medicines in existing studies [ 27 , 28 , 29 , 30 ]. There are some reports about fingerprint analysis of Danshen to characterize the whole chemical profile [ 31 , 32 , 33 , 34 , 35 ], but in those studies thorough chemometric analysis has not been performed on complex and rich chromatographic peak data to assess their quality, and chemical markers have not been picked as the most significant variables to distinguish Danshen samples of different quality.…”
Section: Introductionmentioning
confidence: 99%
“…Chemometric analysis, using techniques such as principal component analysis (PCA), has become an effective approach in the quality evaluation of TCMs and TCMPs [ 32 , 33 ]. From the PCA score plot, significant separation among different samples was observed, and the loadings plot could pick out the potential discriminatory components from differences evaluation as well.…”
Section: Resultsmentioning
confidence: 99%